Mapping Method from Object-relational Database to RDF（S） - Lu, Jia-wen; Yan, Li (Ji suan ji ke xue, 2021)
With the development of intelligent information technology, knowledge graph has been widely used in intelligent search and other research area.The information in the knowledge map is generally represented by the data model of RDF（S）.The construction of knowledge graph needs to extract information from different data sources and database is an important data source that cannot be ignored.Nowadays, object-relational databases are widely used and contain rich semantic information, but research on constructing RDF（S） from object-relational databases is few.This paper puts forward formal definitions of object-relational databases and RDF（S） data and proposes mapping rules for constructing RDF（S） data from object-relational databases.The mapping rules not only consider the object-oriented semantics of the database, but also consider constraints, which can fully extract semantic information contained in the database.Finally, a mapping tool named ORDB2 RDF is implemented to verify the correctness of the mapping rules